Psychospołeczne implikacje bezrobocia - Harasim, Konrad (De Securitate et Defensione. O Bezpieczeństwie i Obronności, 2016)
The purpose of the article is to present the negative psychosocial effects that are caused by unemployment. The subject of the article is a contemporary identification of the consequences of unemployment: disintegration and social exclusion, lack of opportunities to satisfy basic material needs; destructive influence on the well-being of the individual and its environment; the phenomenon of social pathology. The consequences of unemployment negatively affect the individuals sense of security: the personal, social, and economic one. Mass character of the scale of unemployment and its dynamics require constant monitoring and action taken by the public policy, especially that the largest group of unemployed people is the so-called NEET generation – educated young people.